2020
DOI: 10.1111/aor.13711
|View full text |Cite
|
Sign up to set email alerts
|

Control of ventricular unloading using an electrocardiogram‐synchronized pulsatile ventricular assist device under high stroke ratios

Abstract: Pulsatile ventricular assist devices (pVADs) yield a blood flow that imitates the pulsatile flow of the heart and, therefore, could diminish the adverse events related to the continuous flow provided by the ventricular assist devices that are commonly used. However, their intrinsic characteristics of larger size and higher weight set a burden to their implantation, that along with the frequent mechanical failures and thrombosis events, reduce the usage of pVADs in the clinical environment. In this study, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Since no thromboembolism was observed in the autopsy findings, we assumed that the thrombi formed in the oxygenator were not flushed out of the oxygenator by the pulsatile flow but were inhibited at the very early stage of the thrombus‐formation cascade. Various studies on pulsatile flow in ECMO and ventricular assist devices have been reported not only in basic research but also in clinical applications 31–33 . However, although improvement of gas exchange capacity of oxygenators with the pulsatile flow has been reported, 34–36 we could not find any reports on the inhibitory effect of pulsatile flow on thrombus formation.…”
Section: Discussionmentioning
confidence: 81%
“…Since no thromboembolism was observed in the autopsy findings, we assumed that the thrombi formed in the oxygenator were not flushed out of the oxygenator by the pulsatile flow but were inhibited at the very early stage of the thrombus‐formation cascade. Various studies on pulsatile flow in ECMO and ventricular assist devices have been reported not only in basic research but also in clinical applications 31–33 . However, although improvement of gas exchange capacity of oxygenators with the pulsatile flow has been reported, 34–36 we could not find any reports on the inhibitory effect of pulsatile flow on thrombus formation.…”
Section: Discussionmentioning
confidence: 81%
“…Commercialized pump systems and valves were considered, but no system was found that allows for sufficiently fast switching of the flow direction and the generation of sufficiently high pressure for the actuation of the utilized soft robotic end actuators and balloon catheters. In order to meet the above requirements, we developed a dedicated in vivo actuation device that is based on a linear voice coil motor (LVCM) [26], [27]. A schematic of the custom actuation device and its control structure for the later in vivo application is shown in Figure 3.…”
Section: Development Of the Hydraulic Actuation Devicementioning
confidence: 99%
“…Nonetheless, recent studies have reported strong evidence that the lack of pulsatility can negatively affect the endothelial and peripheral vascular function (25-27) and, hence, increase the risk of non-surgical bleeding (28). Additionally, various studies highlight the better control of ventricular unloading and patient's hemodynamics when VADs that effectively resemble the pulsatile flow conditions are deployed (29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%